Design of Housing Marketing Information System KPR Putra Residence Web-Based - Melda Agnes Manuhutu; Lulu Jola Uktolseja; Arik Novitaningsih; Yerrynaldo Loppies (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The progress and development of information technology in this globalization era is growing rapidly, one of which is the internet. Internet can facilitate the public in getting information in various ways, one of which is information about housing promotion. Home is a primary need which must be fulfilled by every human being, family and even an organization. The purpose of this study is to design a website-based mortgage promotion information system (case study: PT. Mulia Indah Permatasari). The development model of this system is waterfall model. As for the workings of the system created, the components that support the making of this system is this system uses the XAMPP software as a local server, MySQL as the database and the programming language used is PHP.